Drug Interactions with Complementary and Alternative Medicine and Dietary Supplements - Basnet, S; Adhikary, P; Aryal, B (Journal of Chitwan Medical College, 2013)
Complementary and Alternative Medicine (CAM) is a group of diverse medical and health care systems, practices and products that are not presently considered to be a part of conventional medicine. Primary reasons for the use are to relieve symptoms associated with chronic, even terminal illnesses or the side effects of conventional treatments or having a holistic health philosophy or cultural belief. In Nepal, the Ayurvedic system is most widespread and reasons for this had no or less side effect as well as more effective for chronic patients. Drug interactions can occur at the pharmaceutical, pharmacodynamic, or pharmacokinetic level. Herbals and dietary supplements containing St John’s Wort (Hypericum perforatum), ginkgo (Ginkgo biloba), kava (Piper methysticum), digitalis (Digitalis purpurea), willow (Salix alba), magnesium, calcium and iron were documented to have the most interactions with individual medications. Warfarin, insulin, aspirin, digoxin, and ticlopidine had the greatest number of reported interactions with those preparations. Since, half of the Nepalese populations use CAM therapy, the healthcare professionals should pay attention towards such interactions. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8433 Journal of Chitwan Medical College Vol.3(2) 2013 1-3